Synthesis and characterization of zirconium oxides for use as antimicrobial additives in paints - Arreche, Romina Andrea (2015)
Zirconia is a multifunctional material widely used. Its important properties such as high chemical resistance, thermal stability and high mechanical toughness have turned these materials into object of study within fields such as the optics, electronics, magnetism, among others. In recent years, the chemical properties of zirconium oxide have been used, mixed with silicon in order to obtain mixed oxides, more stable and robust, with the final application on toughening of ceramics. These properties are related to the degree of mixing of the components at molecular level, therefore, the linking between Si-O-Zr. Considering the effective antimicrobial capacity of silver nanoparticles, their incorporation into different materials is very interesting, acting as biocides. The objective of this work is to obtain zirconium oxides by the sol-gel technique, using zirconium n-propoxide as precursor, and also study the effect of different solvents (water:ethanol), the use of various acid catalysts in the synthesis, acetic acid and a heteropolyacid (HPA), as the phosphomolybdic acid (H3PMo12O40), in the physicochemical properties of the obtained solids. Finally, the addition of a silver salt was carried out into the sample with acetic acid and heteropolyacid as catalyst in order to incorporate it as antimicrobial filler in paints. The obtained materials were characterized by SEM, XRD, FT-IR, textural properties through the absorption of N2 (SBET) and potentiometric titration with n-butylamine. Homogeneous solids were obtained in all the synthesis with acetic acid as catalysts. In addition, x-ray diffraction diagrams of amorphous solids were observed. The values obtained of surface areas are influenced by the variables of synthesis. The characteristic bands of zirconia were observed by FTIR in the solids synthesized. The results show that the solids environmentally synthesized are promising additives for use in paints.